Improvement of critical current density in YBa2Cu3O7-δ superconductor added with Pr2O3 and graphene oxide - Baharuddin, Nur Atikah (2017)
The effect of nanoparticle praseodymium oxides (Pr2O3) and graphene oxides (GO) addition on the critical current density, Jc of YBa2Cu3O7-δ was studied. Both nanoparticles added acted as pinning center to enhance the transport critical current density (Jc). YBa2Cu3O7-δ superconductor was prepared by co-precipitation method with addition of Pr2O3 are 0.00, 0.02, 0.03, 0.04 and 0.05, while addition of GO are 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5 weight percentage (wt.%). Co-precipitation process is based upon a simple control of the chemistry of the cation solution and precipitation with oxalic acid. The effect of nanoparticles addition on electrical superconducting properties (Tc and Jc), phase formation and structural properties, microstructure and surface morphology including the elemental distribution analysis were studied. YBa2Cu3O7-δ with Pr2O3 nanoparticle addition showed a maximal value of Tc at 82 K for 0.01 wt % addition and give smallest grain sizes 0.38 μm. However, Jc shows improvements in Pr2O3 addition of 0.03 wt.% with the highest Jc, 9678 A/cm2. YBa2Cu3O7-δ with GO nanoparticle showed an improvement value of Tc when GO added wt.% increase to 0.5 wt.%, 88 K. However, YBa2Cu3O7-δ added with GO give a vice versa results in Jc, which has a lower Jc than YBa2Cu3O7-δ with Pr2O3 nanoparticles addition. X-ray Diffraction (XRD), showed Y-123 phase exist in all samples which proves by the XRD and Energy Dispersive X-rays (EDX) profiling. Both nanoparticles added in YBa2Cu3O7-δ show increased values of Tc and Jc towards the optimum wt. % of addition and decreased after further addition of nanoparticles.